FACILITATION APPROACH IMPLEMENTATION IN THE COGNITIVE ACTIVITY FORMATION OF PRESCHOOL AND PRIMARY EDUCATION STUDENTS - RUDENSKYI, Rostyslav; PYSARCHYK, Oksana (HUMANITARIAN STUDIES: HISTORY AND PEDAGOGY, 2024)
Abstract. The article notes that the creation of a holistic educational and developmental environment of an educational institution is possible only in an effectively adjusted system of relations between the subjects of the student and the teacher. Establishing such relations requires not only updated content of education or modern space of the institution, but first, defining the conceptual framework, justifying the initial conditions and approaches that underlie the effectiveness of this system of relations. It is indicated that one of the approaches of modern preschool and primary education is the facilitation approach, which requires scientific interpretation. It has been found that a modern teacher-facilitator needs to master the facilitation competence, which includes the following components: the ability to formulate clear and accessible instructions for children, the ability to organize children's independent activities, the ability to engage in joint activities without coercion, the ability to ask open questions and summarize children's ideas, situational planning skills, flexibility in the implementation of the educational process, etc. The theoretical basis and methodology for implementing the facilitation approach to the formation of cognitive activity of senior preschoolers and primary school students are substantiated by comparing the key aspects of the traditional educational and facilitation process and identifying the interrelationships between them. It has been determined that the essence of facilitation is the process of facilitating, simplifying, and guiding the interpersonal interaction of participants to a certain, agreed upon and accepted by all subject’s result. It is generalized that in the educational process of preschool and primary education it is advisable to introduce elements of direct, indirect facilitation and their combinations with the help of facilitation tools in the following types of student activities: game activities, communication, project activities, grouping students into teams/groups, completing tasks in groups, presenting the results of group work, facilitating speakers' reports and discussing the results of team/group work. It has been found that in the process of facilitation it is possible to influence the development student's cognitive activity, which will significantly improve the nature of interpersonal interaction between the participants of the process, by mastering their cognitive independence and active involvement. It is summarized that during the adaptation and game cycle of primary education, when there should be an organic transition from the leading type of game to learning, junior schoolers should gain experience of independent work and knowledge acquisition, master cognitive independence, forming a stable type of cognitive activity. It is the development of cognitive activity and independence that the facilitation approach to education promotes.